Efektifitas Pembelajaran Bahasa Arab dengan Strategi Qiraah Jahriyah untuk Meningkatkan Pembelajaran Maharah Qiraah di MTs Zainul Hasan Genggong Pajarakan - Sugianto, Muhammad; Zaini, Bahruddin (LP3M UNZAH GENGGONG, 2022)
Abstract The process of learning Arabic is to increase maharah qira'ah for students of MTs Zainul Hasan Genggong who are under the auspices of the Zainul Hasan Genggong Islamic Boarding School. This study aims to explain and describe how the qira'ah learning process occurs and how the qira'ah learning outcomes of MTs Zainul Hasan Genggong students. This research is included in the type of linguistic research by emphasizing on understanding Arabic texts based on good and correct reading pronunciation rules. The method used in this study is qualitative to see the learning process that occurs, the data sources in this study are Arabic teachers and students at MTs Zainul Hasan Genggong, especially teachers who teach Maharah Qira'ah. The results of the study found students. Likewise with Qira'ah which emphasizes understanding the contents of the reading text from the results of research found in the field using a reading test, it is found that understanding of the reading text is quite good. Keywords: effectiveness, learning, Qira'ah